International Adoption Comparative Legal Research – Child Adoption in Georgia, Issues for Legislative Harmonization - Mindiashvili, Nino (European Scientific Journal, ESJ, 2018)
International Adoption is a subsidiary measure for the protection of children – it only becomes an option if reintegrating a child into his/her extended family or adoption in the child’s country of origin is not possible. What are the rules that must be followed in intercountry adoption cases?What are each participant’s rights and duties? Who is allowed to adopt a child? What is the procedure? What are the opportunities and the risks if you become involved in providing a child with a proper home for the first time? This article aims to answer these questions and many others. It is intended as a source of ideas for professionals or authority involved in adoption.